Սուրիական Ճեզիրէն եւ նորագաղթ հայերը (Թէլ Պրագ) - Ֆիշենկճեան, Անի (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Провозглашение Мустафой Кемалем Ататюрком Турецкой Республики не положило конец государственной политике антиармянского преследования. Напротив, политической основой вновь сформированного правительства было укрепление и распространение турецкого национализма. The proclamation of the Republic of Turkey by Mustafa Kemal Ataturk did not put an end to the state policy of anti-Armenian persecutions. On the contrary, the policy of the newly-formed government was the strengthening and deployment of the Turkish nationalism․
Keywords: Armenian immigration